Determinant of Output Growth during Pandemic Covid-19 in Six ASEAN Countries: Panel Data Approach between 2020:I and 2021: I - Farah Wulandari Pangestuty; Abdul Manap Pulungan (Program Studi Pendidikan Ekonomi Universitas Pamulang, 2023)
Covid-19 pandemic is blamed to be the one which steal one country’s generation because of its severe impacts in economic growth. The study investigates the determinants of output growth during Covid-19 pandemic in six ASEAN countries e.i. Indonesia, Singapore, Thailand, Malaysia, the Philippines, and Viet Nam over the 2020:I - 2021:I period. This study utilises secondary data with panel regression pooled least square (common effect) estimation technique to answer whether the independent variables e.i. central bank policy rate (cbpr), total positive case of Covid-19 (covid), and credit default swap (cds) have significant impact on those six ASEAN countries.We find that cbpr, covid, and cds impact significantly (critical value 95%) on output growth in the six Asian countries. However, cbpr and cds still become puzzle which have a positive relationship with output growth, that might be normal tot the crisis situation. We recommend to include innovation as one prominent factor boosting the growth.